MODERN ADVANCES IN THE DIAGNOSIS OF ACUTE CALCULOUS CHOLECYSTITIS (A literature review) - Khakimov M.Sh.; Karimov R.A.; Murodov A.M. (Central Asian Journal of Medicine, 2023)
Diagnostic methods for acute calculous cholecystitis continue to evolve. Among the most common abdominal pathologies, acute calculous cholecystitis requires astute clinical judgment, highly accurate and correct diagnosis, adequate treatment, and timely surgical intervention. A wide range of diagnostic and grading programs have been developed, most remarkably the Tokyo Guidelines, but some recent clinical validation studies have questioned their applicability in practice. The timing of surgical intervention is another area that requires further study and improvements in the diagnosis of this disease.